2004
DOI: 10.1016/j.vetimm.2004.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oligodeoxyribonucleotides that induce interferon (IFN)-α in the pig and the phenotype of the IFN-α producing cells

Abstract: The immunostimulatory effects of oligodeoxyribonucleotides (ODN) containing unmethylated CpG dinucleotides (CpG-ODN) in certain base contexts have been extensively studied in man and mice. One major action is their ability to trigger production of massive amounts of interferon-alpha (IFN-alpha) by plasmacytoid dendritic cells (PDC), also referred to as natural IFN-alpha/beta producing cells (NIPC). The present study using porcine PBMC activated by CpG-ODN or plasmid DNA revealed a considerable variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…Cultures of poPBMCs (200 l) were established in microtiter plates (Nunc; Roskilde, Denmark) at a final concentration of 5 ϫ 10 6 cells/ml in the presence of specific ODN preparations, control plasmid DNA, or virus preparations at concentrations previously determined as optimal for IFN-␣ induction (11,19). Cell culture supernatants were collected after 20 h of incubation at 37°C, 7% CO 2 , and stored at Ϫ20°C until further use.…”
Section: Preparation Of Popbmcsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cultures of poPBMCs (200 l) were established in microtiter plates (Nunc; Roskilde, Denmark) at a final concentration of 5 ϫ 10 6 cells/ml in the presence of specific ODN preparations, control plasmid DNA, or virus preparations at concentrations previously determined as optimal for IFN-␣ induction (11,19). Cell culture supernatants were collected after 20 h of incubation at 37°C, 7% CO 2 , and stored at Ϫ20°C until further use.…”
Section: Preparation Of Popbmcsmentioning
confidence: 99%
“…It is still unknown how PCV2 becomes activated, but in clinically diseased pigs, such as those presenting with the PCV2-associated disease postweaning multisystemic wasting syndrome, a number of organs, including the liver, lungs, and kidneys, are affected, and an abundance of the PCV2 antigen can be detected in the lesions (2). In vitro studies have confirmed that PCV2 can persist in porcine myeloid DCs and porcine plasmacytoid DCs (PDCs), also referred to as natural interferon-producing cells (NIPCs) (11,43), with no effect on their viability or expression of differentiation antigens. However, the ability of PDCs to produce the cytokines alpha interferon (IFN-␣) and tumor necrosis factor alpha is clearly diminished in the presence of PCV2 (46).…”
mentioning
confidence: 99%
See 3 more Smart Citations